Identifying themes to inform nursing decisions when caring for patients with acute exacerbation of chronic obstructive pulmonary disease on noninvasive ventilation: A qualitative descriptive study - Farmer, Mary Jo S.; Callahan, Christine; Riska, Karen; Hughes, Ashley M.; Stefan, Mihaela S. (Research in nursing & health, 2022)
Prior studies analyzing patient experience with noninvasive ventilation (NIV) found the most impactful interaction that patients remembered was with nurses, however a survey of nurses regarding the management of patients treated with NIV has shown that most nurses felt unprepared to care for these sick patients. Our qualitative descriptive study explored the current nursing experience using NIV as a treatment for acute exacerbation of chronic obstructive pulmonary disease (AECOPD). Nine (n = 9) subject matter expert nurses practicing in a variety of clinical settings participated in semi‐structured interviews. The COnsolidated criteria for REporting Qualitative research checklist was followed for interview development. Interview transcripts were subsequently analyzed using deductive thematic analysis. Themes identified from the interviews pertained to patient assessment, novice nurses' need for clinical support, team communication, and nursing education. Improving interprofessional team communication and collaboration skills, and implementing guidelines for NIV utilization were specified as essential components of NIV education for nurses. Even though the nursing role in the care of AECOPD NIV patient could be institution dependent, the themes presented in our study are useful in identifying opportunities for NIV nursing education and areas for further research. Patient or Public Contribution: Nurses served as interviewees for this study.